2017
DOI: 10.1177/0021998317712569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volume fraction of reinforcement phase on mechanical behavior of ultra-high-temperature composite consisting of iron matrix and TiB2 particulates

Abstract: Recently, ultra-high-temperature ceramics have received abundance attention due to growing demand of new materials for extreme service conditions. In this study, titanium diboride particles as an ultra-high-temperature ceramic material have been used to reinforce iron matrix to fabricate a metal matrix composite. Iron–titanium diboride composite samples with different volume fractions of titanium diboride fabricated using powder metallurgy route. Physical, microstructural and mechanical properties of metal mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Currently, composite materials are widely used in various kinds of applications and a large share of composites are using fibers as its reinforcement. [1][2][3][4][5][6][7] Depending on the sources, fibers can be classified into two categories: synthetic fiber and natural fiber. Despite offering some lucrative features, the noxious impacts of non-biodegradable synthetic fiber in nature and less feasibility are the issues for which the modern world is looking for its replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, composite materials are widely used in various kinds of applications and a large share of composites are using fibers as its reinforcement. [1][2][3][4][5][6][7] Depending on the sources, fibers can be classified into two categories: synthetic fiber and natural fiber. Despite offering some lucrative features, the noxious impacts of non-biodegradable synthetic fiber in nature and less feasibility are the issues for which the modern world is looking for its replacements.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO has been widely used in the cosmetic and plastic industry to improve some specific properties of composites such as UV absorption, thermal stability, and antibacterial activity . It has been reported that the incorporation of ZnO into different polymers may result in the formation of new materials with unique structure and properties .…”
Section: Introductionmentioning
confidence: 99%
“…Significant correlations of strain rates with linear head acceleration for brain, brainstem, dura, and skull were found and are presented in Figure 9a-d. These linear regressions were independent of the effects of direction and speed of impactor, as well as the HE mass, distance, direction, and head condition (protection) under blast [65]. The proposed strain rates of brain, brainstem, dura, and skull are, respectively, 1.9 (R = 0.8, p < 0.01), 0.7 (R = 0.9, p < 0.01), 1.18 (R = 0.9, p < 0.001) and 0.7 (R = 0.6, p < 0.01) times of resulting head acceleration by impact.…”
Section: Discussionmentioning
confidence: 91%